Aspectos fisiológicos do fruto de açaí sob armazenamento refrigerado - Stefanini, Thais França (Universidade Federal de São Carlos, 2010)
The açaí berry market has been increasing due to its high calorie characteristic and antioxidant activity, that contributes to diseases prevention. The market growth makes it the center of attention, upcoming the necessity to study its storage, transportation and processing chain. So this study has the objective to analyze the physiology and storage conditions of the açaí berry through measures of respiration, based on temperature and water content, freezing point detection, water potential due to water content function, cohesion of the mesocarp, color of the parenchymal reserve, pH level, acidity and contents of anthocyanins. The respiration based on the temperature of the açaí berry can be fitted by Arrhenius curve with activation energy of 79.6 kJ.mol-1. Q10 values for the açaí berry were between 2 and 3.The metabolism of the açaí berry showed and exponential result related to the reduction in water content. The average freezing temperature was around -3.4 º C, and maximum of -1.8 ° C. The hidroconservation storage reduces oxidation of anthocyanins, due to its low temperature. However, fruits stored in hidroconservation showed possible characteristics of freezing injury and anaerobic conditions, indicated by the presence of aqueous solution produced by the fruit inside the package, reducing the mesocarp cohesive force, changing the parenchyma s reserves colour and acidity variations. The refrigerator storage leads to a fast decrease in total anthocyanins. The gas permeability of the used packaging process reduces the anaerobic process, and its higher storage temperature decreases the symptoms of freezing injury, but increases fruit water loss.
Physiological aspects of açaí berry in cold storage
Keywords: Biotecnologia; Euterpe oleracea; Respiração; Congelamento; Potencial de água; Açaí - qualidade; Euterpe oleracea; Respiration; Freezing; Water potential; Quality; Hidroconservation; Mesocarp cohesion; CIENCIAS BIOLOGICAS::FISIOLOGIA